2022
DOI: 10.1155/2022/4766252
|View full text |Cite|
|
Sign up to set email alerts
|

Effect Evaluation of Comfort Nursing Materials Assisted Nursing for Patients with Advanced Malignant Tumor

Abstract: In order to explore the effect of comfort care on patients with advanced malignant tumors assisted by bioceramics, 82 patients with advanced malignant tumors admitted to a cancer hospital were selected as the research object control group: 26 males and 15 females and the observation group: 25 males and 16 females. The control group was given routine care, and the observation group was given comfort care on the basis of the control group. The quality of life (QLQ-C30 functional scale) and nursing satisfaction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%